Analisis Manajemen Kebencanaan Badan Penanggulangan Bencana Daerah Kota Bekasi Dalam Pelaksanaan Penanggulangan Bencana Banjir - Achmad Fachrezi; Indra Aditya; Evi Priyanti (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2026)
Management Agency (BPBD) of Bekasi City in flood disaster mitigation. Bekasi City, which is frequently affected by floods due to high rainfall, poor drainage, and massive development, requires an effective mitigation strategy. This research uses a descriptive qualitative approach to examine the comprehensive implementation of disaster management, from the pre- disaster, during-disaster, and post-disaster phases. Data collection was conducted through interviews, observation, and documentation. The results show that in the pre-disaster phase, the Bekasi City BPBD carries out various preparedness efforts such as forming Disaster- Resilient Villages, providing rubber boats, and conducting socialization to the community. Early warnings are given through direct observation and the dissemination of information using loudspeakers or WhatsApp groups. In the emergency response phase, BPBD conducts evacuations with rubber boats and provides logistical assistance. However, challenges exist, such as a lack of emergency aid and some residents' refusal to evacuate. In the post-disaster phase, BPBD collaborates with other agencies to clean up mud, collect data on losses, and provide psychosocial support and trauma healing services to victims. The study concludes that despite the efforts, disaster management still faces challenges that need to be improved to create a more disaster-resilient Bekasi.